Impacts of COVID-19 on Life in Different Countries: A Systematic Review - Pacheco, Aniceto da Conceição; Exposto, Levi Anatolia S.M. (International Journal Labs, 2021)
Currently, the challenge for WHO and many countries are finding effective drugs to defeat the virus or vaccines that can be used in healthy individuals to prevent them from becoming infected. As there is no effective drug or vaccine, the best procedures currently are control of the source of infection, early diagnosis, isolation, and supportive care. For individuals, good personal hygiene and avoiding crowded places will help to prevent Coronavirus infection. The main purpose of conducting this study is to provide information, descriptions, ideas/ideas about the impact of COVID-19 on people's lives in various countries based on reference sources, both international journals, novels, textbooks, and reports. The writing of this Systematic Review uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method which is carried out systematically by following the stages or procedures of the Systematic Review. The impact of the pandemic in Asia is more sensitive than in countries in the Australia/Oceania region or the European region. Middle-income and low-income countries need to be more prudent in managing the COVID-19 pandemic to have better or equal effectiveness with developed or high-income countries.